2011
DOI: 10.1016/j.virol.2010.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Defining the human immunodeficiency virus type 1 transmission genetic bottleneck in a region with multiple circulating subtypes and recombinant forms

Abstract: The Mbeya region of Tanzania has a genetically complex HIV epidemic with multiple subtypes and recombinant forms circulating, together with a high frequency of dual infections with more than one subtype. This study aimed to determine whether this impacted the HIV-1 transmission bottleneck. A total of 210 env sequences from 22 participants were generated from recently infected women from Mbeya using the single genome amplification approach. Participants were infected with subtypes C (n=9), A (n=4), or D (n=1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…URFs of HIV-1 with different recombination patterns have been reported previously in Tanzania [10], [16], [36], [38], [71]. No viral sequences closely related to the HIV-1 CRF10_CD reported previously in Tanzania [34], [37], [38] have been found in this study, suggesting no selective advantage of CRF10_CD in this population.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…URFs of HIV-1 with different recombination patterns have been reported previously in Tanzania [10], [16], [36], [38], [71]. No viral sequences closely related to the HIV-1 CRF10_CD reported previously in Tanzania [34], [37], [38] have been found in this study, suggesting no selective advantage of CRF10_CD in this population.…”
Section: Discussionsupporting
confidence: 47%
“…The HIV-1 subtype profile was similar in the Mbeya region with the exception of subtype A2 and CRF10_CD which have not been found in the region [10]. Furthermore, HIV-1 multiple variants were reported in 23% of a high-risk population of female bar and hotel workers with acute HIV-1 infection in the Mbeya region of Tanzania [16].…”
Section: Introductionmentioning
confidence: 71%
“…Phusion High Fidelity polymerase was used for the second-round PCR with the primers ENV A (5¢-GCTTAG GCATCTCCTATGGCAGGAAGAA-3¢) and ENV N (5¢-CTGCCAATCAGGGAAGTAGCCTTGTGT-3¢). 8 The final PCR product (*3.2 kb) was ligated into the pcDNA3.1.V5-His TOPO TA vector according to the manufacturer's instructions (Invitrogen). Plasmid DNA was isolated from individual randomly picked white bacterial colonies and digested with the HindIII and NotI restriction enzymes (New England BioLabs) to screen for the presence of the insert.…”
Section: Introductionmentioning
confidence: 99%
“…Functional Env clones were constructed from nine participants infected with either HIV-1 subtype C (n = 6) or recombinant CD (n = 2) or AD (n = 1) who were previously found to be infected with a single variant (Nofemela et al, 2011). All clones were identical to the consensus of the SGA-derived env amplicons, and assumed to represent the T/F virus responsible for clinical infection (Keele et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 212 Env sequences from 22 participants (n = 10 sequences per participant) generated using single genome amplification (SGA) indicated that sixteen participants were infected with a single infectious unit at transmission (Nofemela et al, 2011). Neighbour-joining trees and HIGHLIGHTER plots ( http://www.hiv.lanl.gov) of the SGA sequences were used to identify the sequence of the T/F virus, and the amplicons identical to the consensus sequence were cloned from nine acute stage participants as part of the Vaccine Immune Monitoring Consortium, Collaboration for AIDS Vaccine Discovery (VIMC -CAVD) (http://www.…”
Section: Cohort Descriptionmentioning
confidence: 99%